Influence of Stefan blowing on the flow and heat transfer of non-Newtonian Jeffrey nanofluid over an unsteady stretching sheet - D. Thenmozhi; M. Eswara Rao; B. Nagabhushanam Reddy; J. Arthy; Muhammad Jawad; Gabriella Bognár; Walid Abdelfattah (Results in Engineering)
This study investigates the unsteady boundary layer flow and heat transfer of a non-Newtonian Jeffrey nanofluid over a stretching sheet with the influence of Stefan blowing or suction, magnetic field, thermal radiation and porous medium. The two-phase Buongiorno model is employed to account for nanoparticle effects, including Brownian motion and thermophoresis. The governing partial differential equations (PDEs) are transformed into a system of ordinary differential equations (ODEs) using similarity transformations and solved numerically using the fourth-order Runge-Kutta (RK-4) method combined with the shooting technique. The model provides insight into the physical behavior of nanofluids in porous media under time-dependent and magnetohydrodynamic (MHD) effects, which are critical for industrial applications such as heat exchangers, solar thermal collectors, and electronic cooling systems.